2020
DOI: 10.1038/s41436-020-00944-7
|View full text |Cite
|
Sign up to set email alerts
|

Correction: KAT6A Syndrome: genotype–phenotype correlation in 76 patients with pathogenic KAT6A variants

Abstract: The original version of this Article did not include Tatjana Bierhals, Maja Hempel, Jessika Johannsen, and Davor Lessel in the list of authors for their contribution to data collection and analysis. This has now been corrected in both the PDF and HTML versions of the Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…At 16 weeks, cardiac findings were confirmed and trio ES was performed, which revealed a heterozygous de-novo mutation, c.4663A > G (p.Ser1555Gly), in exon 17 of the KAT6A gene, which fulfilled the ACMG criteria PS2, PM1, PM2, PP3 and BP1-Class 4 and was classified as likely pathogenic 2 . Kennedy et al reported a similar variant, p.Ser1555Arg, in a cohort of 76 cases with Arboleda-Tham syndrome 3 . Subsequent examination at 18 + 5 weeks confirmed the cardiac findings in addition to bilateral pyelectasis and a head shape suggestive of brachycephaly with early signs of possible craniosynostosis (Figure 2b).…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…At 16 weeks, cardiac findings were confirmed and trio ES was performed, which revealed a heterozygous de-novo mutation, c.4663A > G (p.Ser1555Gly), in exon 17 of the KAT6A gene, which fulfilled the ACMG criteria PS2, PM1, PM2, PP3 and BP1-Class 4 and was classified as likely pathogenic 2 . Kennedy et al reported a similar variant, p.Ser1555Arg, in a cohort of 76 cases with Arboleda-Tham syndrome 3 . Subsequent examination at 18 + 5 weeks confirmed the cardiac findings in addition to bilateral pyelectasis and a head shape suggestive of brachycephaly with early signs of possible craniosynostosis (Figure 2b).…”
mentioning
confidence: 87%
“…This analysis showed a de-novo heterozygous deletion of exons 13-17 within the KAT6A gene, which was classified as pathogenic as per the joint consensus recommendation of the American College of Medical Genetics and Genomics (ACMG) and the Clinical Genome Resource (ClinGen) 2 . The classification was assigned based on the deletion of multiple exons in a loss-of-function-intolerant gene, absence of similar deletions in population databases, previous reporting of multiple loss-of-function variants in the deleted region in patients with KAT6A syndrome 3 and the de-novo occurrence. The specific codes applied were 2E (PVS1_vs), 3A and 4C.…”
mentioning
confidence: 99%
See 3 more Smart Citations